Two faces of party system stability: Programmatic change and party replacement. (September 2021) - Borbáth, Endre
Despite extensive research on party system stability, the concept is often reduced to the survival of existing parties. This article argues for introducing programmatic stability as a separate dimension and shows how the combination of party replacement and programmatic instability shapes patterns of party competition. Based on their interaction, the article distinguishes four ideal types: stable systems, systems with empty party labels, systems with ephemeral parties, and general instability. The empirical analysis relies on media data and proposes a new measure of programmatic stability to study its interaction with party replacement in fifteen European countries during the period of the economic crisis. As the article shows, the two dimensions shape the transformation of party systems in northwestern, southern, and eastern Europe. Relying on multidimensional scaling, the article analyzes in detail the cases of the United Kingdom, Romania, Ireland, and Latvia to showcase party competition under different conditions of systemic instability.